Association between long-term exposure to air pollution and mortality in France: A 25-year follow-up study. (December 2015) - Bentayeb, Malek; Wagner, Verene; Stempfelet, Morgane; Zins, Marie; Goldberg, Marcel; Pascal, Mathilde; Larrieu, Sophie; Beaudeau, Pascal; Cassadou, Sylvie; Eilstein, Daniel; Filleul, Laurent; Le Tertre, Alain; et al.
Abstract: Introduction: Long-term exposure to air pollution (AP) has been shown to have an impact on mortality in numerous countries, but since 2005 no data exists for France. Objectives: We analyzed the association between long-term exposure to air pollution and mortality at the individual level in a large French cohort followed from 1989 to 2013. Methods: The study sample consisted of 20, 327 adults working at the French national electricity and gas company EDF-GDF . Annual exposure to PM10, PM10–2.5, PM2.5, NO2, O3, SO2, and benzene was assessed for the place of residence of participants using a chemistry-transport model and taking residential history into account. Hazard ratios were estimated using a Cox proportional-hazards regression model, adjusted for selected individual and contextual risk factors. Hazard ratios were computed for an interquartile range (IQR) increase in air pollutant concentrations. Results: The cohort recorded 1967 non-accidental deaths. Long-term exposures to baseline PM2.5, PM10-25, NO2 and benzene were associated with an increase in non-accidental mortality (Hazard Ratio, HR = 1.09; 95% CI: 0.99, 1.20 per 5.9 μg/m 3, PM10-25 ; HR = 1.09; 95% CI: 1.04, 1.15 per 2.2 μg/m 3, NO2 : HR = 1.14; 95% CI: 0.99, 1.31 per 19.3 μg/m 3 and benzene: HR = 1.10; 95% CI: 1.00, 1.22 per 1.7 μg/m 3 ).The strongest association was found for PM10 : HR = 1.14; 95% CI: 1.05, 1.25 per 7.8 μg/m 3 . PM10, PM10-25 and SO2 were associated with non-accidental mortality when using time varying exposure. No significant associations were observed between air pollution and cardiovascular and respiratory mortality. Conclusion: Long-term exposure to fine particles, nitrogen dioxide, sulfur dioxide and benzene is associated with an increased risk of non-accidental mortality in France. Our results strengthen existing evidence that outdoor air pollution is a significant environmental risk factor for mortality. Due to the limited sample size and the nature of our study (occupational), further investigations are needed in France with a larger representative population sample. Highlights: We assessed air quality using deterministic and geostatistical modeling approach. We tested several lags of exposure including time-varying exposures. We analyzed data of a large French cohort followed-up from 1989 to 2013. Long-term exposure to several air pollutants was associated with all-cause mortality.